Video essays : curating and transforming film education through artistic research - Sendra, Estrella (2020)
This article seeks to foster reflection on film pedagogy and research, encouraging academics to engage in artistic research and teaching methods. It specifically focuses on the video essay as a teaching and learning method, one that requires the willingness to take risks, but also, that can lead to a transformative experience in a still hierarchical educational system. The increasing openness to video essays in film journals shows an awareness of the way in which artistic research may contribute to decolonise academia. The practice of video essays leads to an inclusive, collaborative and polyphonic research environment, which dismantles the idea of a film canon. It contests the privileged position of the written ‘text’, when this is just understood as the written word. It also contributes to blurring the distance between the status of students and that of researchers. It invites them to assimilate work practices, curating and filmmaking, which sometimes happen simultaneously, curating through filmmaking. This article shares the example of the design of the video essay as a creative assessment method for two film modules in the MA Global Cinemas and the BA Creative Arts at SOAS, University of London. It stresses the importance of connecting research, practice and teaching, that is, the recursive study of film through film. It suggests that through making video essays class members become co-curators of the course, where learning is a multi-directional and collaborative experience.